Analysis of the possibility to control the inertia of the thermoelectric cooler - Zaykov, Vladimir; Mescheryakov, Vladimir; Zhuravlov, Yurii (Eastern-European Journal of Enterprise Technologies, 2017)
We examined a model of transient processes for the thermoelectric cooler and performed its analysis when the device operated under a non-stationary mode. It is shown that the consideration of various factors influencing the transition process of a thermoelectric cooler comes down to the control over temperature of a thermoelement junction and to the variation of a heat load. The developed model connects thermophysical and structural parameters of the thermoelement, external load and operating current. The model employs the constraints: branches of thermoelements possess identical thermophysical parameters, side surfaces of the cooler are thermally insulated. An analysis of the model revealed the influence of working current density on the temperature difference and the inertia of thermoelements. We determined conditions under which, by changing the magnitude of operating current, it is possible to minimize the time of transition of temperature difference of the thermoelement to the stationary state, typical of the systems for ensuring heat regimes of thermally-loaded components. The results obtained could serve as a basis for the creation of control system over dynamic characteristics of the thermoelectric cooler